Levodopa / opicapone as a complement to STN-DBS in clinical practice. A retrospective single-centre analysis. - Moritz A. Loeffler; Philipp Klocke; Idil Cebi; Alireza Gharabaghi; Daniel Weiss (eNeurologicalSci)
Objective: Deep brain stimulation of the subthalamic nucleus (STN-DBS) is a well-established treatment option in Parkinson's disease with motor and non-motor fluctuations allowing for postoperative reduction of dopaminergic medication. However, evidence is scarce on optimal medication adjustments following STN-DBS implantation. Opicapone allows for long-lasting inhibition of the catechol-O-methyltransferase (COMT) thereby enabling more constant dopaminergic stimulation compared to levodopa alone. However, especially COMT inhibitors are regularly discontinued after STN-DBS surgery. In this single-centre retrospective analysis, we aimed to analyse the clinical phenotype of patients selected for opicapone treatment following STN-DBS implantation and to define clinical determinants of patients requiring more intense dopamine-stabilising strategies after STN-DBS implantation. Methods: A patient cohort treated with STN-DBS + levodopa + opicapone (n = 16) was compared to an age-matched control cohort without opicapone treatment at baseline before and ≥ 5 months post-surgery. As main outcomes we assessed the MDS-UPDRS III and IV scores and reduction of the cumulative dopaminergic medication quantified by the levodopa equivalent dosages (LED). Results: Whilst the MDS-UPDRS III (median [min – max]) in patients with STN-DBS as well as anatomical electrode positions did not differ significantly between the opicapone 20 [4–40] and control cohort 14 [1–44], the patients selected for opicapone treatment showed a significantly higher degree of dyskinesias already preoperatively as reflected by a UPDRS-IV A subscore of 2 [0–4] compared to controls 0 [0–4]. Postoperatively, the opicapone cohort showed stronger motor fluctuations MDS-UPDRS IV 6 [0–14] compared to the controls 0 [0−10], albeit without statistical significance. Moreover, the opicapone cohort showed significantly less reduction of dopaminergic medication (−36.4 % vs. -46.2 % in the control cohort) following STN-DBS implantation independent from the intake of dopamine agonists. Conclusion: These results indicate a clinical phenotype characterised by more motor fluctuations requiring a more stable dopamine replacement therapy to address the patients' disease biology. In these cases, levodopa + COMT inhibition by opicapone represents a therapeutic approach but determination of the potential clinical benefit requires further prospective studies.